Óptima gestión de la demanda para estaciones de recarga de vehículos eléctricos en micro-redes inteligentes - Vergara Naranjo, Verónica Rosa (2017)
At the present paper, the insertion of electric vehicles (EVs) is considered as an alternative to reduce the emission of greenhouse gases, for this reason it is necessary to analyze the charging stations of electric vehicles to mitigate the entrance of new load in hours Peak of electrical demand of the country, realizing an optimal management of the demand using unconventional energies. Through six points for simultaneous charging at each recharging station, taking advantage of solar radiation in the city of Quito for photovoltaic energy production, as well as storing its surplus at storage batteries. When managing a demand with uncertainty in each recharging station, an optimum dispatch of energy will be performed every hour in two different scenarios winter and summer , taking into account the maximum and minimum capacities as well as the costs of each energy source through a heuristic with Linear programming giving priority to the distributed generation generated in each recharging station leaving the last option the supply with power of the distribution network, in this manner it mitigates the charge of the batteries of the electric vehicles in rush hours.